Results of Achieve the Effectiveness of Regional Revenue Agency in Local Tax Services in Barru District - Dewi Utari; Gita Susanti; Badu Ahmad (Institute of Computer Science (IOCS), 2021)
The midst of the many needs for regional financing and the complexity of the needs of the citizens, of course, the regional government must be able to explore its own financial sources as an autonomous region so that the implementation of government functions can run effectively and efficiently, namely in the field of government and services to the community. In indonesia itself over the last few years, tax revenue has increased significantly, both in nominal and as a percentage of the total state revenue. On the other hand, in general, the percentage of taxpayers is still very small compared to the total population in Indonesia In this study, the author uses scott's theory. In analyzing the effectiveness of regional revenue agency in local tax services in barru district,